Commercial utilities and future perspective of nanomedicines - Malviya, Rishabha; Fuloria, Shivkanya; Verma, Swati; Subramaniyan, Vetriselvan; Sathasivam, Kathiresan V.; Kumarasamy, Vinoth; Hari Kumar, Darnal; Vellasamy, Shalini; Meenakshi, Dhanalekshmi Unnikrishnan; Yadav, Shikha; Sharma, Akanksha; Fuloria, Neeraj Kumar (PeerJ, 2021)
The present review aims to describe the commercial utilities and future perspectives of nanomedicines. Nanomedicines are intended to increase precision medicine and decrease the adverse effects on the patient. Nanomedicines are produced, engineered, and industrialized at the cellular, chemical, and macromolecular levels. This study describes the various aspects of nanomedicine such as governing outlooks over high use of nanomedicine, regulatory advancements for nanomedicines, standards, and guidelines for nanomedicines as per Therapeutic Goods Administration (TGA). This review also focuses on the patents and clinical trials based on nanoformulation, along with nanomedicines utilization as drug therapy and their market value. The present study concludes that nanomedicines are of high importance in biomedical and pharmaceutical production and offer better therapeutic effects especially in the case of drugs that possess low aqueous solubility. The factual data presented in this study will assist the researchers and health care professionals in understanding the applications of nanomedicine for better diagnosis and effective treatment of a disease.
Keywords: Nanomedicines; Nanotechnology; Drug therapy; Nanoparticles; Disease treatment